Method for detection of pathogenic bacteria from indoor air microbiome samples using high-throughput amplicon sequencing - Nor Husna, Mat Hussin; Siew, Shing Wei; Mohd Norhafsam, Maghpor; Gan, Han Ming; Hajar Fauzan, Ahmad (Elsevier B.V., 2024)
The exposure of the air microbiome in indoor air posed a detrimental health effect to the building occupants compared to the outdoor air. Indoor air in hospitals has been identified as a reservoir for various pathogenic microbes. The conventional culture-dependent method has been widely used to access the microbial community in the air. However, it has limited capability in enumerating the complex air microbiome communities, as some of the air microbiomes are uncultivable, slow-growers, and require specific media for cultivation. Here, we utilized a culture-independent method via amplicon sequencing to target the V3 region of 16S rRNA from the pool of total genomic DNA extracted from the dust samples taken from hospital interiors. This method will help occupational health practitioners, researchers, and health authorities to efficiently and comprehensively monitor the presence of harmful air microbiome thus take appropriate action in controlling and minimizing the health risks to the hospital occupants. Key features; • Culture-independent methods offer fast, comprehensive, and unbias profiles of pathogenic and non-pathogenic bacteria from the air microbiomes. • Unlike the culture-dependent method, amplicon sequencing allows bacteria identification to the lowest taxonomy levels.